Chemotherapy Near the End of Life for Chinese Patients with Solid Malignancies - Sheng, Jin; Zhang, Ya‐Xiong; He, Xiao‐Bo; Fang, Wen‐Feng; Yang, Yun‐Peng; Lin, Gui‐Nan; Wu, Xuan; Li, Ning; Zhang, Jing; Zhai, Lin‐Zhu; Zhao, Yuan‐Yuan; Huang, Yan; et al. (The oncologist (Dayton, Ohio), 2017)
Introduction There are increasing concerns about the negative impacts of chemotherapy near the end of life (EOL). There is discrepancy among different countries about its use, and little is known about the real‐world situation in China. Patients and Methods This retrospective study was conducted at six representative hospitals across China. Adult decedents with a record of advanced solid cancer and palliative chemotherapy were consecutively screened from 2010 through 2014. The prevalence of EOL chemotherapy within the last 1 month of life was set as the primary outcome. The correlations among EOL chemotherapy, clinicopathological features, and overall survival (OS) were investigated. Results A total of 3,350 decedents who had had cancer were consecutively included; 2,098 (62.6%) were male and the median age was 56 years (range, 20–88). There were 177 (5.3%), 387 (11.6%), and 837 (25.0%) patients who received EOL chemotherapy within the last 2 weeks, 1 month, and 2 months of life, respectively. We identified inferior OS (median OS, 7.1 vs. 14.2 months; hazard ratio, 1.37; 95% confidence interval [CI], 1.23–1.53; p < .001), more intensive treatments (e.g., admitted to intensive care unit [ICU] in the last month of life, received cardiopulmonary resuscitation and invasive ventilation support), and hospital death (odds ratio, 1.53; 95% CI, 1.14–2.06; p = .005) among patients who received continued chemotherapy within the last month compared with those who did not. However, subgroup analyses indicated that receiving oral agents correlated with fewer ICU admissions and lower rates of in‐hospital death. Conclusion This study showed that EOL chemotherapy is commonly used in China. Intravenous chemotherapy at the EOL significantly correlated with poor outcomes and the role of oral anticancer agents warrants further investigation. Implications for Practice The role of chemotherapy toward the end of life (EOL) in patients with solid cancers is debatable. This article is believed to be the first to report the current prevalence of EOL chemotherapy in China. This study found that, compared with oral anticancer agents, intravenous chemotherapy at the EOL was significantly associated with poor outcomes. Therefore, the role of oral anticancer agents at the EOL stage deserves further investigation. 摘要 背景. 人们对临终（EOL）化疗负面影响的关注程度日益增加。EOL化疗在不同国家的应用情况不尽相同, 尚不清楚中国的实际情况。 方法. 在中国不同地区的6家代表性医院开展本项回顾性研究。于2010‐2014年期间连续筛选有晚期实体瘤和姑息化疗记录的成年死者。主要指标为生命最后1个月内进行EOL化疗的发生率。考察了EOL化疗、临床病理学特征与总生存期（OS）之间的相关性。 结果. 连续纳入共计3 350例癌症死亡患者, 其中2 098例（62.6%）为男性, 中位年龄为56岁（范围：20‐88岁）。分别有177例（5.3%）、387例（11.6%）和837例（25.0%）患者在生命最后2周、1个月和2个月内接受EOL化疗。我们发现, 与生命最后1个月内未持续接受化疗的患者相比, 化疗患者的OS更短[中位OS：7.1个月 vs. 14.2个月；风险比：1.37；95%置信区间（CI）：1.23‐1.53；p＜0.001]、治疗强度更大[例如在生命最后1个月入住重症监护室（ICU）、接受心肺复苏术和给予有创通气支持]且院内死亡率更高（比值比：1.53；95%CI：1.14‐2.06；p=0.005）。但亚组分析显示, 口服药物治疗可降低ICU入住率和院内死亡率。 结论. 本研究表明, EOL化疗在中国应用普遍。EOL时接受静脉化疗与不良预后之间存在显著相关性, 而口服抗癌药物的作用仍有待于进一步研究。 对临床实践的提示：关于实体瘤患者临终（EOL）化疗的作用仍有争议。本文首次报道了EOL化疗在中国的应用情况。研究发现, 与口服抗癌药物相比, EOL时接受静脉化疗与不良预后显著相关。因此, 有必要进一步研究在EOL阶段采取口服抗癌药物治疗的作用。 The prevalence of chemotherapy use toward the end of life (EOL) for patients with solid cancers was studied in China. Correlations among EOL chemotherapy, clinicopathological features, and overall survival (OS) were investigated. EOL chemotherapy was associated with reduced OS, more aggressive care measures, and higher in‐hospital death rates. Oral anticancer agents were associated with fewer intensive care‐unit admissions and lower in‐hospital death rates than intravenous therapy.